2015
DOI: 10.1038/nchembio.1960
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric regulation of G protein–coupled receptor activity by phospholipids

Abstract: Lipids are emerging as key regulators of membrane protein structure and activity. Such effects can either be attributed to modification in bilayer properties (thickness, curvature and surface tension) or to binding of specific lipids to the protein surface. For G Protein-Coupled Receptors (GPCRs), the effect of phospholipids on receptor structure and activity remains poorly understood. Here we reconstituted purified β2-adrenergic receptor in High-Density-Lipoparticles to systematically characterize the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
282
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(298 citation statements)
references
References 42 publications
14
282
2
Order By: Relevance
“…The lipid composition of the membrane is a key determinant of the allosteric modulation of receptor function for some receptors (37,39,53). However, in the case of EnvZ, we observed no significant differences in enzymatic activity between the physiological E. coli lipids and the nonbacterial phospholipid DOPC.…”
Section: Discussion Lipids As Allosteric Modulators Of Membrane Protecontrasting
confidence: 53%
See 2 more Smart Citations
“…The lipid composition of the membrane is a key determinant of the allosteric modulation of receptor function for some receptors (37,39,53). However, in the case of EnvZ, we observed no significant differences in enzymatic activity between the physiological E. coli lipids and the nonbacterial phospholipid DOPC.…”
Section: Discussion Lipids As Allosteric Modulators Of Membrane Protecontrasting
confidence: 53%
“…Similar allosteric modulation of receptor function has been demonstrated in diverse membrane protein families, including G-protein-coupled receptors, receptor tyrosine kinases, and proton channels (37,39,(41)(42)(43)(44), as well as soluble cytoplasmic proteins containing lipid-targeting domains (45,46). Lipids impact the structure and function of membrane-embedded or membrane-associated proteins either through bulk effects mediated by the phospholipid bilayer or through binding of lipid molecules at specific sites (40,(47)(48)(49)(50).…”
Section: Discussion Lipids As Allosteric Modulators Of Membrane Protementioning
confidence: 67%
See 1 more Smart Citation
“…Recently, relevant phospholipids were found to affect GPCR function. In β 2 -adrenergic receptors reconstituted in high-density lipoparticles, for instance, phosphatidylgycerol markedly favored agonist binding and facilitated receptor activation, whereas phosphatidylethanolamine favored antagonist binding and stabilized the inactive state of the receptor ( Dawaliby et al, 2016). These data suggested that phospholipids could act as direct allosteric modulators of GPCR activity.…”
Section: Rm and Hmnsmentioning
confidence: 76%
“…These contacts play important roles in membrane protein folding, structure, and function (1). Binding of lipids to specific sites has been observed in crystal structures (2), and increasing evidence suggests that membrane lipids play a critical functional role in a variety of membrane protein classes, including channels (3)(4)(5)(6), transporters (7), G-protein coupled receptors (8), and receptor tyrosine kinases (9).…”
Section: Introductionmentioning
confidence: 99%